Analisis Upaya Perlindungan Hukum Terhadap Konsumen Pengguna Shopee Dalam Transaksi Belanja Online - Miftahul Husna Siregar; Irsalina Rizki Nasution (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The purpose of this study is to analyze the forms, efforts, and obstacles of legal protection for consumers in online shopping transactions on Shopee. Using a normative juridical approach, this descriptive research aims to illustrate the related legal phenomena. Based on Law No. 8 of 1999 and Law No. 19 of 2016, Shopee requires sellers to provide clear product descriptions. Consumer protection includes the prohibition of harmful standard clauses and the obligation for sellers to ensure product conformity. Shopee also mandates that buyers pay on time, granting sellers the right to cancel transactions if payment is not made. Challenges include complicated return processes and slow verification. Users can optimize services, file complaints, and resolve disputes.